Thermal diffusion upon magnetic field convection of nano-enhanced phase change materials in a permeable wavy cavity with crescent-shaped partitions - Aly, Abdelraheem M.; Raizah, Zehba; El-Sapa, Shreen; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal (Elsevier, 2022)
Control of heat transfer and fluid flow by using different shaped materials for different forces and boundary conditions brings advantages for energy efficiency. The present study is examined the effects of the thermal radiation on Magnetohydrodynamic (MHD) thermosolutal convection of Nano-Enhanced Phase Change Materials (NEPCMs) suspension in a horizontal wavy porous cavity with embedded high-temperature crescents. Using these types of heaters in a NEPCM under radiation and the magnetic field is the main novelty of this work. The Incompressible Smoothed Particle Hydrodynamics (ISPH) method established on a time-fractional derivative is employed to manage the suggested problem. The main simulations revealed that the alteration of a thermal radiation parameter changes the phase change material and enhances the nanofluid flow. The time-fractional derivative is playing a good role in reaching the steady-state and affecting the phase change material at the initial time steps. The movements of a NEPCM are reduced by an increment in the Hartmann number, time-fractional derivative, and solid volume fraction. The nanofluid speed decreases by 26.32% as a increases from 0.95 to 1.
Keywords: Thermal radiation; Crescent; Horizontal wavy cavity; ISPH; NEPCM; Magnetic field; Fractional derivative